An Epidemiological Study of Oral Mucosal Lesions in Karnataka State, India - K. V. V Prasad; S B Javali; G Rajesh; A Jithendra (Wolters Kluwer Medknow Publications, 2004)
This article presents oral mucosal lesions findings from a state oral health survey of Karnataka, India. A total of 46,579 subjects aged 1-4 to 65+ years were selected by using multistage-cluster-stratified random sampling method and subjects were examined by 32 dentists trained in standardized clinical diagnostic criteria for oral mucosal lesions. In the present study, 7.53% of subjects had one or more oral mucosal lesions, in which, male subjects (9.41 %) had a significantly higher prevalence of lesions compared to female subjects (4.38%); urban subjects (11.61%) had a significantly higher prevalence than rural subjects (5.01 %) and the Christian subjects had a significantly higher prevalence of lesions than the Hindus, Muslims and others (F=211.594, <0.001, S). The observed prevalence of oral mucosal lesions increased with age (r=0.8174, P<0.05, S), which is statistically significant. The most prevalent lesions observed were Leukoplakia (1.73%), Lichen planus (2.02%) Ulceration (0.73%), Candidiasis (0.94%) and Abscess (1.05%). The maximum number of lesions was seen in sulci (7.33%) and the minimum number of lesions was seen in lips (0.02%). Differences in prevalence were analyzed by sex, religion, location and geographical area.